(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article is about congenital heart flaws. Congenital heart flaws are the result of incorrect formation of heart and large blood vessels in the early stages of fetal development. The article information about genetic and external factors that cause these diseases, their emergence, and the various accessiolas of chromosoma anomalies and pregnancy (viral infections, malicious habits, mother chronic diseases) given. It is also explained in detail about the effects of congenital heartvisions, their effect on the body, clinical forms, and most common forms, aortic stench, etc.. The article is the importance of timely diagnosis and treatment of these diseases and the need for prenatal preventive measures.